(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
Physical Education teachers’ professional self-improvement comprises motivational, activity, informational and operational, gnostic, and communicative components. The level of these components can be assessed by the demand and motivational, functional, theoretical and methodical, communicative, as well as informational and operational criteria. It has been experimentally proved that the following pedagogical conditions contribute to Physical Education teachers’ professional selfimprovement: taking into account teachers’ individual and age peculiarities; encouraging Physical Education teachers to self-improvement in the process of professional activities; provision of choosing personal trajectory of self-improvement taking into account the guidelines for professional development. The designed pedagogical technology aimed at Physical Education teachers’ professional self-improvement consists of four blocks: targeted, content, organizational and active, and control and effective ones. The implementation of this pedagogical technology results in positive dynamics of Physical Education teachers’ professional self-improvement which has been experimentally proved.